Plateau Indian Ways with Words : the Rhetorical Tradition of the Tribes of the Inland Pacific Northwest - Monroe, Barbara Jean, 1948- (Pittsburgh series in composition, literacy, and culture., 2014)
"In Plateau Indian Ways with Words, Barbara Monroe makes visible the arts of persuasion of the Plateau Indians, whose ancestral grounds stretch from the Cascades to the Rockies, revealing a chain of cultural identification that predates the colonial period and continues to this day"--